Asking the experts: A focus group and review on eyewitness memory in the multicultural context of South Africa [version 1; peer review: 2 approved, 1 approved with reservations] - Laura Anne Weiss; Annelies Vredeveldt; Eva A. J. van Rosmalen (Open Research Europe)
Background The purpose of this study was to create a theoretical overview of cultural differences and intercultural communication in eyewitness interviews in a multicultural context. Specifically, we focused on the context of South Africa, one of the most culturally diverse countries in the world. Methods We conducted a critical review of the relevant literature and organized a focus group with 12 international experts from different academic fields and cultural informants from South Africa to identify and deepen our understanding of cultural factors that may play a role in eyewitness interviews. We differentiated between eyewitness factors (e.g., emotional response) and the interaction between interviewer and eyewitness (e.g., miscommunication). Results The main factors that emerged from the analysis were: individualism/collectivism, perception and presentation of facts, influence of demographics, presentation of self and personal style, subjective descriptions, emotional response, language, influencing behaviors in high-/low-context cultures, characteristics of the interaction and miscommunication. Each of these factors has a number of subcategories. Conclusions The present article contributes to our understanding of cultural differences in eyewitness memory and intercultural communication by systematically collecting and analysing expert knowledge and situating it within the existing literature for the first time.